A polycrystalline strong boroaluminate glass-ceramic and its preparation method

Through specific proportions of raw materials and preparation processes, polycrystalline strong transparent boron aluminate microcrystalline glass is prepared, which solves the challenges of high-crystalline boron aluminate glass in terms of hardness, crack resistance and fracture toughness, and achieves the High drop resistance, scratch resistance and high transmittance.

CN118619553BActive Publication Date: 2025-02-11安徽晖光玻璃科技有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410859376.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-28
Publication Date
2025-02-11
Estimated Expiration
2044-06-28

AI Technical Summary

Technical Problem

High crystallinity boron aluminate glass has challenges in improving hardness, crack resistance and fracture toughness, and has reduced visible light transmittance, reduced amorphous phase content, and reduced crack resistance.

Method used

Using specific proportions of Li2O, Al2O3, B2O3, BaO, Nb2O5 and Ta2O5 raw materials, after melting, casting, annealing and procedural temperature-controlled crystallization, polycrystalline strong transparent boron aluminate microcrystalline glass is prepared. The main crystal phase is LiAl7B4O17, and the secondary crystal phase is LiTaO3 or LiNbO3.

Benefits of technology

It improves the hardness, fracture toughness and crack resistance of the glass, while maintaining a high visible light transmittance, meeting the high drop resistance and scratch resistance of consumer electronic products for cover glass.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118619553B_ABST
    Figure CN118619553B_ABST
Patent Text Reader

Abstract

The invention discloses a polycrystalline strong and tough boroaluminate microcrystalline glass and a preparation method thereof, belonging to the technical field of microcrystalline glass. Li2CO3, Al2O3, B2O3, BaCO3, Nb2O5 and Ta2O5 are mixed, melted at high temperature, cast and annealed to obtain a base glass without crystallization, and then crystallized by program temperature control to obtain a base glass. The main crystal phase precipitated is LiAl7B4O 17 The secondary crystalline phase is LiTaO3 and / or LiNbO3. The existence of the secondary crystalline phase effectively hinders the expansion of cracks. Since the LiTaO3 or LiNbO3 crystal phase has piezoelectric effect, when the glass is impacted by external force, the energy that can cause the glass to be damaged can be partially absorbed by the secondary crystalline phase LiTaO3 or LiNbO3, and part of the destructive stress energy is absorbed and converted through the piezoelectric effect, and part of the crack extension energy is consumed through domain transformation, thereby improving the hardness and fracture toughness of the microcrystalline glass.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of transparent microcrystalline glass, and in particular to a polycrystalline strong boroaluminate microcrystalline glass and a preparation method thereof. Background Art

[0002] Cover glass is an important component in portable electronic devices, mainly used to protect the display module from physical or chemical damage from the outside world. Boroaluminate glass is a new type of cover glass material with great application potential. The composition of this material does not contain SiO 2 This is in contrast to the existing SiO 2 The microstructure of boroaluminate glass is very different from that of high alumina-silicate glass based on B. 2 O 3 and Al 2 O 3 The structure uses the energy absorption transition characteristics of B and Al elements from low coordination to high coordination (Si element does not have this characteristic), which can absorb part of the stress through self-adjustment of the network structure when subjected to external force impact, thereby improving the ability to resist crack generation (CR). After the subsequent crystallization treatment, a large number of crystal phases precipitated in the boroaluminate glass increase the length of the crack path, help dissipate mechanical energy, effectively prevent crack propagation, and improve fracture toughness (K IC ), and with the increase of crystallinity, the fracture toughness increases. In addition, the crystal phase precipitated during the microcrystallization process can also increase the hardness of the glass (generally using Vickers hardness tester, Hv).

[0003] However, high-crystallinity boroaluminate glass faces some problems: first, the visible light transmittance is reduced, and second, the amorphous phase content is reduced, which makes it impossible to give full play to the network adaptive characteristics, resulting in reduced crack resistance. Therefore, how to simultaneously improve the hardness, crack resistance and fracture toughness of boroaluminate glass is a challenge. To this end, the present invention provides a polycrystalline and tough boroaluminate glass-ceramics and a preparation method thereof. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a polycrystalline and tough boroaluminate glass-ceramics and a preparation method thereof, which effectively solves the technical problem that the hardness, crack resistance and fracture toughness of the boroaluminate glass-ceramics cannot be improved at the same time. At the same time, it provides a boroaluminate glass-ceramics with a simple preparation process, high product yield, strong comprehensive drop resistance and scratch resistance of the glass-ceramics, and can meet the use requirements of consumer electronic products for cover glass with high drop resistance and scratch resistance.

[0005] The present invention provides a polycrystalline strong boroaluminate glass-ceramic, characterized in that it is made of the following raw materials in weight percentage: Li 2O: 11%~20%, Al 2 O 3 :15%~35%, B 2 O 3 : 35% to 55%, BaO: 5% to 10%, Nb 2 O 5 :0%~10%,Ta 2 O 5 : 0% to 10%, a total of 100%; the Nb 2 O 5 With Ta 2 O 5 The weight percentages cannot be 0% at the same time.

[0006] As a preferred embodiment, the main crystalline phase of the polycrystalline strong boroaluminate glass-ceramics is LiAl 7 B 4 O 17 The morphology is granular, the precipitation amount is 35-60%, and the average grain size is 20-60nm.

[0007] As a preferred embodiment, the secondary crystalline phase precipitated from the polycrystalline strong boroaluminate glass-ceramics includes LiTaO 3 and / or LiNbO 3 The morphology is granular, the precipitation amount is 7-12%, and the average grain size is 15-30nm.

[0008] As a preferred embodiment, the polycrystalline strong boroaluminate glass-ceramics has a Vickers hardness of 5.0 to 8.2 GPa and a fracture toughness of 0.9 to 1.3 MPa. 1 / 2 The anti-cracking performance value is 15~25N.

[0009] As a preferred embodiment, the transmittance of the polycrystalline strong boroaluminate glass-ceramics in the visible light band of 400 to 800 nm is 85 to 93%.

[0010] The second object of the present invention is to provide a method for preparing the above-mentioned polycrystalline strong and tough boroaluminate glass-ceramics, weighing each raw material according to the mass percentage of the above-mentioned raw materials, mixing them evenly, melting them at 1200-1500°C, casting them, and annealing them at 400-500°C to obtain non-crystallized basic glass, crystallizing the non-crystallized basic glass under programmed temperature control, and cooling them to obtain polycrystalline strong and tough transparent boroaluminate glass-ceramics.

[0011] As a preferred embodiment, the melting treatment time is 1 to 6 hours.

[0012] As a preferred implementation, the annealing treatment time is 1 to 6 hours.

[0013] As a preferred embodiment, the specific method of the programmed temperature control is: raising the temperature to 550-620° C. at a rate of 1.0-10.0° C. / min and keeping the temperature for 5-20 hours.

[0014] As a preferred implementation, after keeping the temperature for 5 to 20 hours, the temperature is raised to 650 to 680° C. at a rate of 8.0° C. / min and kept for 1 to 3 hours, and then cooled along with the furnace.

[0015] Compared with the prior art, the present invention has the following beneficial effects:

[0016] (1) The present invention uses 11% to 20% Li by mass 2 O, 15%~35%Al 2 O 3 , 35%~55%B 2 O 3 ,5%~10%BaO,0%~10%Nb 2 O 5 , 0%~10%Ta 2 O 5 After raw material mixing, high temperature melting, casting and annealing, the uncrystallized basic glass is obtained, and then the crystallization treatment is carried out by program temperature control to obtain a polycrystalline, strong and transparent boroaluminate microcrystalline glass. The main crystalline phase precipitated is LiAl 7 B 4 O 17 , and the morphology is granular, which effectively improves the hardness and fracture toughness of the glass; the secondary crystalline phase is LiTaO 3 or / and LiNbO 3 The morphology is also granular. The existence of the secondary crystalline phase can not only play the role of hindering the expansion of the crystal phase to the crack, but also 3 or LiNbO 3 The crystalline phase is a typical crystal with piezoelectric effect (converting mechanical energy into electrical energy). When the glass is impacted by external force, it generates energy that can cause the glass to break, which can be partially replaced by the secondary crystalline phase LiTaO 3 or LiNbO 3 It absorbs and converts part of the destructive stress energy through the piezoelectric effect, consumes part of the crack extension energy through domain transformation, and plays a role in further improving the hardness and fracture toughness of the microcrystalline glass.

[0017] (2) The polycrystalline strong boroaluminate glass-ceramics prepared by the present invention has a Vickers hardness of 5.0 to 8.2 GPa and a fracture toughness of 0.9 to 1.3 MPa m 1 / 2 In addition, the overall crystallinity of the microcrystalline glass is 42% to 70% (wherein the main crystalline phase is LiAl 7 B4 O 17 The crystallinity is 35% to 60%, the crystallinity of the secondary crystalline phase is 7% to 12%), and the residual amorphous phase content is 30% to 58%. Thanks to the excellent crack resistance of the residual amorphous phase, the crack resistance of the microcrystalline glass can be maintained at a high level of 15 to 25N. The size of the crystallization phase of the microcrystalline glass can be controlled within 100nm (15 to 60nm), and the absorption and scattering of visible light are small, which can make visible light effectively pass through the glass. The transmittance of the microcrystalline glass in the visible light band (400 to 800nm) is 85% to 93%. In summary, the microcrystalline glass has strong comprehensive capabilities in preventing hard objects from penetrating, limiting crack formation, and hindering crack propagation. It can effectively improve the drop resistance and scratch resistance of the cover glass, and has good application prospects in the field of cover glass for consumer portable smart electronic devices.

[0018] (3) In the process of preparing polycrystalline strong boroaluminate glass-ceramics according to the present invention, the melting temperature is 1200-1500°C, which can effectively save energy compared with the melting temperature of traditional high-alumina silicate glass (1500-1700°C). At the same time, the bubble discharge effect is good during glass melting, and the glass obtained by casting has few defects and a high yield rate.

[0019] (4) The preparation method of the polycrystalline strong boroaluminate microcrystalline glass provided by the present invention is simple in process and has a high product yield. The microcrystalline glass has strong comprehensive drop resistance and scratch resistance, and can meet the high requirements of consumer electronic products for cover glass. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is the DSC graph of the polycrystalline strong boroaluminate glass-ceramics prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0021] In order to enable those skilled in the art to better understand the technical solution of the present invention and implement it, the present invention is further described below in conjunction with specific examples, but the examples are not intended to limit the present invention. The following test methods and detection methods, unless otherwise specified, are conventional methods; the reagents and raw materials, unless otherwise specified, are commercially available.

[0022] The high crystallinity boroaluminate glass mentioned in the background technology of the present invention faces some problems: first, the visible light transmittance is reduced, and second, the amorphous phase content is reduced, which cannot give full play to the network adaptive characteristics, resulting in reduced crack resistance and inability to simultaneously improve the hardness, crack resistance and fracture toughness of boroaluminate microcrystalline glass. Based on the above technical problems, the present invention provides a polycrystalline strong and tough boroaluminate microcrystalline glass and a preparation method thereof, with a mass percentage of 11% to 20% Li 2 O, 15%~35%Al2 O 3 , 35%~55%B 2 O 3 ,5%~10%BaO,0%~10%Nb 2 O 5 , 0%~10%Ta 2 O 5 After raw material mixing, high-temperature melting, casting and annealing, the non-crystallized basic glass is obtained, and then the crystallization treatment is carried out by programmed temperature control to obtain a polycrystalline, strong and transparent boroaluminate microcrystalline glass.

[0023] The main crystalline phase of the polycrystalline strong transparent boroaluminate glass-ceramics is LiAl 7 B 4 O 17 , and the morphology is granular, which effectively improves the hardness and fracture toughness of the glass; the secondary crystalline phase is LiTaO 3 or / and LiNbO 3 The morphology is also granular. The existence of the secondary crystalline phase can not only play the role of hindering the expansion of the crystal phase to the crack, but also 3 or LiNbO 3 The crystalline phase is a typical crystal with piezoelectric effect (converting mechanical energy into electrical energy). When the glass is impacted by external force, it generates energy that can cause the glass to break, which can be partially replaced by the secondary crystalline phase LiTaO 3 or LiNbO 3 It absorbs and converts part of the destructive stress energy through the piezoelectric effect, consumes part of the crack extension energy through domain transformation, and plays a role in further improving the hardness and fracture toughness of the microcrystalline glass.

[0024] The technical solution of the present invention is analyzed and explained in detail below.

[0025] The present invention first provides a polycrystalline strong boroaluminate glass-ceramic, which is made of the following raw materials in weight percentage: Li 2 O: 11%~20%, Al 2 O 3 :15%~35%, B 2 O 3 : 35% to 55%, BaO: 5% to 10%, Nb 2 O 5 :0%~10%,Ta 2 O 5 : 0% to 10%, a total of 100%; the Nb 2 O 5 With Ta 2 O 5 The weight percentages of the above components cannot be 0% at the same time. The synergistic relationship of the above components is as follows:2 O 3 and Al 2 O 3 As an intermediate of the glass network, it helps to build a more complex boroaluminate glass network. Different from traditional silicate glass, the glass network structure constructed by B and Al can take advantage of its variable coordination number when subjected to stress impact (Si in traditional silicate glass does not have this feature), absorb part of the destructive impact energy by changing its coordination state, and at the same time enhance the compactness of the network, thereby improving the mechanical strength of the glass. In addition, B 2 O 3 As a typical low melting point compound, a large amount of B in the glass component 2 O 3 The addition of can significantly reduce the melting temperature of glass, making it easier to melt and shape the glass, which is conducive to the discharge of bubbles generated during melting, reducing glass defects and improving the yield rate. 2 O, as a network exo-oxide, interrupts the dense glass network structure formed by B and Al, providing sufficient mobile network space for the movement of atoms in the subsequent crystallization process of the glass. 7 B 4 O 17 and LiTaO with piezoelectric effect 3 or LiNbO 3 The presence of Li atoms is essential as the main constituent element in the crystal phase. 2 The lithium ions provided by O can be used as a source of ion exchange, which provides the possibility of strengthening the glass strength through ion exchange in the future. The addition of BaO is beneficial to improve the high-temperature viscosity characteristics of the glass, making the melting and molding of the glass at high temperatures smoother, and also plays a certain role in improving the crystallization performance. 2 O 5 and Ta 2 O 5 As nucleating agents, the main function of these two raw materials is to promote the precipitation of crystals in the glass, especially to control the LiTaO with piezoelectric effect in this example. 3 or LiNbO 3 The precipitation of the crystalline phase can also adjust the size, type, morphology and content of the crystals. By precisely controlling these parameters, the microstructure of glass and glass-ceramics can be optimized, thereby improving their macroscopic properties and ultimately achieving the goal of polycrystalline toughness.

[0026] The main crystalline phase of the polycrystalline strong boroaluminate glass-ceramics is LiAl 7 B 4 O 17The polycrystalline strong boroaluminate glass-ceramics contains LiTaO 3 and / or LiNbO 3 The polycrystalline strong boroaluminate glass-ceramics has a Vickers hardness of 5.0 to 8.2 GPa and a fracture toughness of 0.9 to 1.3 MPa. 1 / 2 The crack resistance value is 15 to 25N; the transmittance of the polycrystalline strong boroaluminate glass-ceramics in the visible light band of 400 to 800nm ​​is 85 to 93%.

[0027] The present invention also provides a method for preparing the above-mentioned polycrystalline strong boroaluminate glass-ceramics, wherein each raw material is weighed according to the mass percentage of the above-mentioned raw materials, mixed, melted and cast at 1200-1500°C, when the melting temperature is lower than 1200°C, the raw materials cannot be fully melted, forming an uneven glass liquid; when the melting temperature is higher than 1500°C, part of the raw materials will volatilize in large quantities, and the composition of the obtained glass liquid deviates too much from the designed composition. Afterwards, according to the DSC test results, the incompletely cooled and formed glass block obtained by casting is annealed at 400-500°C to obtain an uncrystallized basic glass, and the uncrystallized basic glass is crystallized under program temperature control and cooled to obtain polycrystalline strong and transparent boroaluminate glass-ceramics.

[0028] As a preferred embodiment, the melting treatment time is 1 to 6 hours. If the melting time is longer than 6 hours, some chemical components may volatilize or unnecessary chemical reactions may occur; if the melting time is shorter than 1 hour, the glass liquid may not be homogenized enough, bubbles may not be completely removed, and the obtained base glass may have many internal defects, which may affect the material transmittance and mechanical strength.

[0029] As a preferred embodiment, the annealing time is 1 to 6 hours. If the annealing time is less than 1 hour, it is not enough to completely release all internal stresses, resulting in the glass being prone to breakage in subsequent use; if the annealing time is more than 6 hours, the glass preparation time will be too long, wasting energy and reducing production efficiency.

[0030] As a preferred embodiment, the specific method of program temperature control is: heating to 550-620°C at a rate of 1.0-10.0°C / min and keeping the temperature for 5-20 hours, and cooling with the furnace. Program temperature control helps to evenly distribute heat in the furnace, avoid local overheating, and ensure that the temperature of each part of the material is uniform and consistent; direct and rapid heating will cause uneven heating of the inner and outer layers of the glass raw material, generate huge thermal stress, and cause the glass to crack or break.

[0031] As a preferred embodiment, after keeping the temperature for 5 to 20 hours, the temperature is raised to 650 to 680°C at a rate of 8.0°C / min and kept for 1 to 3 hours, and then cooled with the furnace. Further program heating to the specified temperature can provide sufficient energy to promote the further formation and growth of the crystal nucleus, thereby further optimizing and improving the performance of the microcrystalline glass.

[0032] The technical effects of the present invention are described below through specific embodiments and comparative examples.

[0033] Example 1

[0034] A polycrystalline, strong, transparent boroaluminate glass-ceramic, made of the following raw materials in percentage by mass: Li 2 O: 16%, Al 2 O 3 : 32%, B 2 O 3 :35%,BaO:7%,Nb 2 O 5 : 6%, Ta 2 O 5 : 4%.

[0035] The preparation method of the polycrystalline strong and tough boroaluminate glass-ceramics is as follows: weigh the raw materials of the above mass percentage, mix them evenly, melt them at 1200°C for 1 hour, cast the molten mixture into a mold, and place it in a muffle furnace at 440°C for 5 hours for annealing, and after cooling with the furnace, obtain the non-crystallized basic glass. The non-crystallized basic glass is crystallized by program temperature control, specifically by heating from room temperature to 585°C at a heating rate of 6°C / min, and keeping the temperature for 12 hours, and then cooling with the furnace to room temperature, so as to obtain polycrystalline strong and tough transparent boroaluminate glass-ceramics.

[0036] After testing, the main crystalline phase precipitated in the microcrystalline glass is LiAl 7 B 4 O 17 The precipitation amount is 35%, the morphology is granular, the average grain size is 35nm, and the secondary crystalline phase is LiTaO 3 and LiNbO 3 The precipitation amount is 7%, the morphology is granular, and the average grain size is 20nm. The Vickers hardness of the obtained microcrystalline glass is 5.0GPa and the fracture toughness is 0.9MPa m 1 / 2 The anti-cracking performance value is 25N. In addition, the transmittance of the microcrystalline glass in the visible light band of 400-800nm ​​is 90%.

[0037] Example 2

[0038] A polycrystalline, strong, transparent boroaluminate glass-ceramic, made of the following raw materials in percentage by mass: Li 2 O: 13%, Al 2 O 3 : 30%, B 2 O 3 :40%,BaO:6%,Nb 2 O 5 : 4%, Ta 2 O 5 : 7%.

[0039] The preparation method of the polycrystalline strong and tough boroaluminate glass-ceramics is as follows: weigh the raw materials of the above mass percentage, mix them evenly, melt them at 1300°C for 6 hours, cast the molten mixture into a mold, and place it in a muffle furnace at 500°C for annealing for 6 hours, and cool it with the furnace to obtain a non-crystallized basic glass. The non-crystallized basic glass is crystallized by program temperature control, specifically by heating from room temperature to 560°C at a heating rate of 4°C / min, and keeping it warm for 16 hours, and then cooling it with the furnace to room temperature, thereby obtaining polycrystalline strong and tough transparent boroaluminate glass-ceramics.

[0040] After testing, the main crystalline phase precipitated in the microcrystalline glass is LiAl 7 B 4 O 17 The precipitation amount is 40%, the morphology is granular, the average grain size is 60nm, and the secondary crystalline phase is LiTaO 3 and LiNbO 3 The precipitation amount is 10%, the morphology is granular, and the average grain size is 15nm. The Vickers hardness of the obtained microcrystalline glass is 5.9GPa and the fracture toughness is 1.0MPa m 1 / 2 The anti-cracking performance value is 22N. In addition, the transmittance of the microcrystalline glass in the visible light band of 400-800nm ​​is 85%.

[0041] Example 3

[0042] A polycrystalline, strong, transparent boroaluminate glass-ceramic, made of the following raw materials in percentage by mass: Li 2 O: 13%, Al 2 O 3 : 27%, B 2 O 3 :44%,BaO:8%,Nb 2 O 5 : 3%, Ta 2 O 5 : 5%.

[0043] The preparation method of the above-mentioned polycrystalline strong and tough boroaluminate glass-ceramics is as follows: weigh the raw materials of the above-mentioned mass percentage, mix them evenly, melt them at 1250°C for 2h, cast the molten mixture into a mold, and place it in a muffle furnace at 400°C for 1h for annealing, and after cooling with the furnace, obtain the non-crystallized basic glass. The non-crystallized basic glass is crystallized by program temperature control, specifically by heating from room temperature to 570°C at a heating rate of 3°C / min, and keeping it warm for 6h, then heating to 665°C at a rate of 8.0°C / min and keeping it warm for 2h, and then cooling it to room temperature with the furnace, so as to obtain polycrystalline strong and tough transparent boroaluminate glass-ceramics.

[0044] After testing, the main crystalline phase precipitated in the microcrystalline glass is LiAl 7 B 4 O 17 The precipitation amount is 55%, the morphology is granular, the average grain size is 40nm, and the secondary crystalline phase is LiTaO 3 and LiNbO 3 The precipitation amount is 8%, the morphology is granular, and the average grain size is 25nm. The Vickers hardness of the obtained microcrystalline glass is 7.5GPa and the fracture toughness is 1.2MPa m 1 / 2 The anti-cracking performance value is 17N. In addition, the transmittance of the microcrystalline glass in the visible light band of 400-800nm ​​is 88%.

[0045] Example 4

[0046] A polycrystalline, strong, transparent boroaluminate glass-ceramic, made of the following raw materials in percentage by mass: Li 2 O: 12%, Al 2 O 3 : 25%, B 2 O 3 :48%,BaO:5%,Nb 2 O 5 : 10%.

[0047] The preparation method of the above-mentioned polycrystalline strong and tough boroaluminate glass-ceramics is as follows: weigh the above-mentioned raw materials in the mass percentage, mix them evenly, melt them at 1350°C for 5 hours, cast the molten mixture into a mold, and place it in a muffle furnace at 460°C for annealing for 4 hours, and cool it with the furnace to obtain a non-crystallized basic glass. The non-crystallized basic glass is crystallized by program temperature control, specifically by heating from room temperature to 580°C at a heating rate of 4°C / min, and keeping it warm for 10 hours, then heating to 650°C at a rate of 8.0°C / min and keeping it warm for 1 hour, and then cooling it to room temperature with the furnace to obtain polycrystalline strong and tough transparent boroaluminate glass-ceramics.

[0048] After testing, the main crystalline phase precipitated in the microcrystalline glass is LiAl 7 B 4 O 17 The precipitation amount is 50%, the morphology is granular, the average grain size is 30nm, and the secondary crystalline phase is LiNbO 3 The precipitation amount is 10%, the morphology is granular, and the average grain size is 30nm. The Vickers hardness of the obtained microcrystalline glass is 7.0GPa and the fracture toughness is 1.1MPa m 1 / 2 The anti-cracking performance value is 18N. In addition, the transmittance of the microcrystalline glass in the visible light band of 400-800nm ​​is 91%.

[0049] Example 5

[0050] A polycrystalline, strong, transparent boroaluminate glass-ceramic, made of the following raw materials in percentage by mass: Li 2 O: 11%, Al 2 O 3 : 19%, B 2 O 3 :55%,BaO:5%,Nb 2 O 5 : 7%, Ta 2 O 5 : 3%.

[0051] The preparation method of the polycrystalline strong and tough boroaluminate glass-ceramics is as follows: weigh the raw materials of the above mass percentage, mix them evenly, melt them at 1350°C for 3 hours, cast the molten mixture into a mold, and place it in a muffle furnace at 450°C for annealing for 3 hours, and cool it with the furnace to obtain a non-crystallized basic glass. The non-crystallized basic glass is crystallized by program temperature control, specifically by heating from room temperature to 550°C at a heating rate of 1°C / min, and keeping it warm for 9 hours, and then cooling it with the furnace to room temperature, to obtain polycrystalline strong and tough transparent boroaluminate glass-ceramics.

[0052] After testing, the main crystalline phase precipitated in the microcrystalline glass is LiAl 7 B 4 O 17 The precipitation amount is 45%, the morphology is granular, the average grain size is 20nm, and the secondary crystalline phase is LiTaO 3 and LiNbO 3 The precipitation amount is 10%, the morphology is granular, and the average grain size is 22nm. The Vickers hardness of the obtained microcrystalline glass is 6.8GPa and the fracture toughness is 1.1MPa m 1 / 2 The anti-cracking performance value is 21N. In addition, the transmittance of the microcrystalline glass in the visible light band of 400-800nm ​​is 93%.

[0053] Example 6

[0054] A polycrystalline, strong, transparent boroaluminate glass-ceramic, made of the following raw materials in percentage by mass: Li 2 O: 10%, Al 2 O 3 : 15%, B 2 O 3 : 50%, BaO: 10%, Nb 2 O 5 : 4%, Ta 2 O 5 : 10%.

[0055] The preparation method of the polycrystalline strong and tough boroaluminate glass-ceramics is as follows: weigh the raw materials of the above mass percentage, mix them evenly, melt them at 1400°C for 4 hours, cast the molten mixture into a mold, and place it in a muffle furnace at 470°C for 2 hours for annealing, and cool it with the furnace to obtain the base glass without crystallization. The base glass without crystallization is crystallized by program temperature control, specifically by heating from room temperature to 600°C at a heating rate of 8°C / min, keeping the temperature for 20 hours, and then cooling it with the furnace to room temperature, thus obtaining the polycrystalline strong and tough transparent boroaluminate glass-ceramics.

[0056] After testing, the main crystalline phase precipitated in the microcrystalline glass is LiAl 7 B 4 O 17 The precipitation amount is 52%, the morphology is granular, the average grain size is 30nm, and the secondary crystalline phase is LiTaO 3 and LiNbO 3 The precipitation amount is 12%, the morphology is granular, and the average grain size is 20nm. The Vickers hardness of the obtained microcrystalline glass is 7.9GPa and the fracture toughness is 1.2MPa m 1 / 2 The anti-cracking performance value is 16N. In addition, the transmittance of the microcrystalline glass in the visible light band of 400-800nm ​​is 91%.

[0057] Example 7

[0058] A polycrystalline, strong, transparent boroaluminate glass-ceramic, made of the following raw materials in percentage by mass: Li 2 O: 9%, Al 2 O 3 : 29%, B 2 O 3 :43%,BaO:9%,Ta 2 O 5 : 10%.

[0059] The preparation method of the above-mentioned polycrystalline strong and tough boroaluminate glass-ceramics is as follows: weigh the above-mentioned raw materials in the mass percentage, mix them evenly, melt them at 1400°C for 2 hours, cast the molten mixture into a mold, and place it in a muffle furnace at 470°C for annealing for 4 hours, and cool it with the furnace to obtain a non-crystallized basic glass. The non-crystallized basic glass is crystallized by program temperature control, specifically by heating from room temperature to 620°C at a heating rate of 2°C / min, and keeping it warm for 8 hours, then heating to 680°C at a rate of 8.0°C / min and keeping it warm for 3 hours, and then cooling it to room temperature with the furnace to obtain polycrystalline strong and tough transparent boroaluminate glass-ceramics.

[0060] After testing, the main crystalline phase precipitated in the microcrystalline glass is LiAl 7 B 4 O 17 The precipitation amount is 60%, the morphology is granular, the average grain size is 35nm, and the secondary crystalline phase is LiTaO 3 The precipitation amount is 10%, the morphology is granular, and the average grain size is 25nm. The Vickers hardness of the obtained microcrystalline glass is 8.2GPa and the fracture toughness is 1.3MPa m 1 / 2 The anti-cracking performance value is 15N. In addition, the transmittance of the microcrystalline glass in the visible light band of 400-800nm ​​is 90%.

[0061] Example 8

[0062] A polycrystalline, strong, transparent boroaluminate glass-ceramic, made from the following percentages by mass: Li 2 O: 7%, Al 2 O 3 : 35%, B 2 O 3 :40%,BaO:6%,Nb 2 O 5 : 10%, Ta 2 O 5 : 2%.

[0063] The preparation method of the polycrystalline strong and tough boroaluminate glass-ceramics is as follows: weigh the raw materials of the above mass percentage, mix them evenly, melt them at 1500°C for 6 hours, cast the molten mixture into a mold, and place it in a muffle furnace at 450°C for 2 hours for annealing, and cool it with the furnace to obtain a non-crystallized basic glass. The non-crystallized basic glass is crystallized by program temperature control, specifically by heating from room temperature to 610°C at a heating rate of 10°C / min, and keeping it warm for 5 hours, and then cooling it to room temperature with the furnace to obtain a polycrystalline strong and tough transparent boroaluminate glass-ceramics.

[0064] After testing, the main crystalline phase precipitated in the microcrystalline glass is LiAl7 B 4 O 17 The precipitation amount is 42%, the morphology is granular, the average grain size is 40nm, and the secondary crystalline phase is LiTaO 3 and LiNbO 3 The precipitation amount is 10%, the morphology is granular, and the average grain size is 15nm. The Vickers hardness of the obtained microcrystalline glass is 6.3GPa and the fracture toughness is 1.0MPa m 1 / 2 The anti-cracking performance value is 20N. In addition, the transmittance of the microcrystalline glass in the visible light band of 400-800nm ​​is 88%.

[0065] In order to further illustrate the technical effect of the present invention, the present invention also sets a comparative example, which is as follows:

[0066] Comparative Example 1

[0067] Compared with Example 8, the difference is that Nb is removed. 2 O 5 and Ta 2 O 5 .

[0068] A boroaluminate glass-ceramic, made from the following raw materials in percentage by mass: Li 2 O: 12%, Al 2 O 3 : 40%, B 2 O 3 : 42%, BaO: 6%.

[0069] The method for preparing the boroaluminate glass-ceramics comprises the following steps:

[0070] The raw materials of the above mass percentages were weighed, mixed, melted at 1500°C for 6 hours, the molten mixture was cast into a mold, and placed in a muffle furnace at 450°C for 2 hours for annealing. After cooling with the furnace, a non-crystallized basic glass was obtained. The non-crystallized basic glass was crystallized by program temperature control, specifically by heating from room temperature to 610°C at a heating rate of 10°C / min, and keeping the temperature for 5 hours, and then cooling with the furnace to room temperature, to obtain a transparent boroaluminate microcrystalline glass.

[0071] After testing, the crystalline phase precipitated in the microcrystalline glass is LiAl 7 B 4 O 17 The precipitation amount is 58%, the morphology is granular, and the average grain size is 45nm. The Vickers hardness of the obtained microcrystalline glass is 4.2GPa and the fracture toughness is 0.7MPa m 1 / 2The anti-cracking performance value is 15N. In addition, the transmittance of the microcrystalline glass in the visible light band of 400-800nm ​​is 88%.

[0072] The hardness, fracture toughness, crack resistance, grain size and visible light transmittance of the polycrystalline strong boroaluminate glass-ceramics obtained in Examples 1 to 8 of the present invention and the boroaluminate glass-ceramics prepared in Comparative Example 1 were tested, and the test results are shown in Table 1.

[0073] Table 1 Physical properties of polycrystalline strong boroaluminate glass-ceramics

[0074]

[0075]

[0076] As shown in Table 1, the hardness of the polycrystalline strong transparent boroaluminate glass-ceramics prepared by the present invention is 5.0-8.2 GPa, and the fracture toughness is 0.9-1.3 MPa m 1 / 2 The crack resistance value is 15-25N, and the transmittance in the visible light band is 85-93%. The performance comparison of the microcrystalline glass of comparative example 1 and the performance comparison of embodiment 8 shows that the Nb added in the present invention 2 O 5 and / or 2 O 5 When the base glass is heat treated, it can combine with the Li atoms in the glass composition to form a subcrystalline LiTaO with piezoelectric effect. 3 or LiNbO 3 , thereby further combining with the main crystal phase LiAl 7 B 4 O 17 The polycrystalline strong and tough boroaluminate glass-ceramics are synergistically realized. Without affecting the transmittance, the hardness, fracture toughness and crack resistance of the polycrystalline strong and tough boroaluminate glass-ceramics in the present invention are better than those in the comparative example 1 without adding Nb. 2 O 5 and / or 2 O 5 Glass-ceramics has been significantly improved and has broad application prospects in the field of cover glass.

[0077] In summary, B in the present invention 2 O 3 and Al 2 O 3As an intermediate of the glass network, it helps to build a more complex boroaluminate glass network. Different from traditional silicate glass, the glass network structure constructed by B and Al can take advantage of its variable coordination number when subjected to stress impact (Si in traditional silicate glass does not have this feature), absorb part of the destructive impact energy by changing its coordination state, and at the same time enhance the compactness of the network, thereby improving the mechanical strength of the glass. In addition, B 2 O 3 As a typical low melting point compound, a large amount of B in the glass component 2 O 3 The addition of can significantly reduce the melting temperature of glass, making it easier to melt and shape the glass, which is conducive to the discharge of bubbles generated during melting, reducing glass defects and improving the yield rate. 2 O, as a network exo-oxide, interrupts the dense glass network structure formed by B and Al, providing sufficient mobile network space for the movement of atoms in the subsequent crystallization process of the glass. 7 B 4 O 17 and LiTaO with piezoelectric effect 3 or LiNbO 3 The presence of Li atoms is essential as the main constituent element in the crystal phase. 2 The lithium ions provided by O can be used as a source of ion exchange, which provides the possibility of strengthening the glass strength through ion exchange in the future. The addition of BaO is beneficial to improve the high-temperature viscosity characteristics of the glass, making the melting and molding of the glass at high temperatures smoother, and also plays a certain role in improving the crystallization performance. 2 O 5 and Ta 2 O 5 As nucleating agents, the main function of these two raw materials is to promote the precipitation of crystals in the glass, especially to control the LiTaO with piezoelectric effect in this example. 3 or LiNbO 3 The precipitation of the crystalline phase can also adjust the size, type, morphology and content of the crystals. By precisely controlling these parameters, the microstructure of glass and glass-ceramics can be optimized, thereby improving their macroscopic properties and ultimately achieving the goal of polycrystalline toughness.

[0078] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A polycrystalline strong boroaluminate glass-ceramic, characterized in that: Made of the following raw materials in weight percentage: Li2O: 11%~20%, Al2O3: 15%~35%, B2O3: 35%~55%, BaO: 5%~10%, Nb2O5: 0%~10%, Ta2O5: 0%~10%, totaling 100%; the weight percentages of Nb2O5 and Ta2O5 cannot be 0% at the same time; The main crystalline phase of the polycrystalline strong boroaluminate glass-ceramics is LiAl7B4O 17 , the morphology is granular, the precipitation amount is 35%~60%, and the average grain size is 20~60 nm; The secondary crystalline phase precipitated from the polycrystalline strong boroaluminate glass-ceramics includes LiTaO3 and / or LiNbO3, which is in granular form, with a precipitation amount of 7% to 12% and an average grain size of 15 to 30 nm; The content of residual amorphous phase of the polycrystalline strong boroaluminate glass-ceramics is 30% to 58%; The method for preparing the polycrystalline strong boroaluminate glass-ceramics comprises the following steps: The raw materials are weighed according to the above weight percentages, mixed evenly, melted at 1200-1500°C, cast and annealed at 400-500°C to obtain non-crystallized basic glass, and the non-crystallized basic glass is crystallized under programmed temperature control and cooled to obtain polycrystalline and tough transparent boroaluminate glass-ceramics.

2. The polycrystalline strong boroaluminate glass-ceramics according to claim 1, characterized in that: The polycrystalline strong boroaluminate glass-ceramics has a Vickers hardness of 5.0-8.2 GPa and a fracture toughness of 0.9-1.3 MPa m 1 / 2 The crack resistance value is 15~25 N.

3. The polycrystalline strong boroaluminate glass-ceramics according to claim 1, characterized in that: The polycrystalline strong boroaluminate glass-ceramics has a transmittance of 85-93% in the visible light band of 400-800 nm.

4. The polycrystalline strong boroaluminate glass-ceramics according to claim 1, characterized in that: The melting treatment time is 1 to 6 hours.

5. The polycrystalline strong boroaluminate glass-ceramics according to claim 1, characterized in that: The annealing time is 1 to 6 hours.

6. The polycrystalline strong boroaluminate glass-ceramics according to claim 1, characterized in that: The specific method of the program temperature control is: heating to 550-620°C at a speed of 1.0-10.0°C / min and keeping the temperature for 5-20 hours, and cooling with the furnace.

7. The polycrystalline strong boroaluminate glass-ceramics according to claim 6, characterized in that: After keeping warm for 5-20 hours, heat up to 650-680℃ at a rate of 8.0℃ / min and keep warm for 1-3 hours, then cool with the furnace.

Citation Information

Patent Citations

  • Microcrystal glass material with ultra wide band near-infrared light emission and preparation method of microcrystal glass material

    CN104310786A

  • Boron aluminate microcrystalline glass and preparation method thereof

    CN115448600A